2016
DOI: 10.3389/fnana.2016.00024
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Integration by Corticospinal System

Abstract: The corticospinal (CS) tract is a complex system which targets several areas of the spinal cord. In particular, the CS descending projection plays a major role in motor command, which results from direct and indirect control of spinal cord pre-motor interneurons as well as motoneurons. But in addition, this system is also involved in a selective and complex modulation of sensory feedback. Despite recent evidence confirms that CS projections drive distinct segmental neural circuits that are part of the sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 42 publications
2
27
0
1
Order By: Relevance
“…Disregarding the fact that the different components of CST are involved in different functions (Lemon and Griffith 2005) and activate different sets of spinal interneurons (Ralston and Ralston 1985;Moreno-López et al 2016), considerations on the timing of corticospinal activation suggests 2 scenarios in motor control.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Disregarding the fact that the different components of CST are involved in different functions (Lemon and Griffith 2005) and activate different sets of spinal interneurons (Ralston and Ralston 1985;Moreno-López et al 2016), considerations on the timing of corticospinal activation suggests 2 scenarios in motor control.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…The CST integrates cortical and lower brain processing centers in the motor system, has an important role in modulating sensory information, and may be particularly relevant to motor hyperactivity in ADHD. 46 Altered modulation of sensory information could potentially be involved in HI remission, as the CST contains fibers running from the primary motor, premotor, supplementary motor, somatosensory, parietal and cingulate cortex to the spine and is thus involved in the control of complex voluntary distal movements. 47 Correspondingly, the persistence of HI could, indeed, result in increased FA in CST through time.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study is the first to bring insight on sensorimotor integration in the trunk motor cortex. This is of fundamental importance since many studies have demonstrated that sensory feedback to the motor cortex is critical during locomotion and recovery of function after spinal cord injury (2,35,53,(62)(63)(64) Indeed, low amplitude tactile stimulation of dorsal trunk did not impact trunk M1. On the other hand, high amplitude stimulation of both the forelimbs and hindlimbs, conveying proprioceptive information, did reach trunk M1.…”
Section: Integration Of Sensorimotor Information Within Trunk M1 Is Nmentioning
confidence: 99%